Diverse Attitudes for Writing Art Histories of Korea: The Impact of the Colonial Period on the Research of Korean Art - Mecsi, Beatrix (WILAYAH: The International Journal of East Asian Studies, 2013)
The abstract is not available. To access, please order the printed version or browse the electronic version of this article.